STUDI EKSPERIMENTAL PERANGKAT UJUNG SAYAP PADA PESAWAT 19 PENUMPANG - Sinung Tirtha; Teuku M Ichwanul H; Ardanto Ardanto; Dana Herdiana; Agus Aribowo (Politeknik Penerbangan Surabaya, 2020)
Winglet devices are design to improve aerodynamic performance of the wing. Its design is intended to minimized drag that produced by wing tip vortices. Wingtip device itself has various type. Experimental study was carried out to observe effect of winglet implementation to the aerodynamic performance of the wing. Four type of wingtip devices was tested by means of wind tunnel testing to find out the optimum design that provide better impact on aerodynamic improvement. The result shows that design number 3 provide highest effect on increasing lift to drag ratio of the wing.